The decolorization effect by Aspergillus sp. 3 on Goldfish opercular beats - Ratna Stia Dewi; Fitria Ayudi Ulfimaturahmah; Khusnul Khotimah (Journal of Microbial Systematics and Biotechnology, 2019)
Batik effluent had high toxicity to aquatic organisms. Dye decolorization is a process used to reduce color density. Fungi which used for decolorization was Aspergillus sp 3. This study aimed to investigate the ability of fungi on decolorization of 3 kinds of batik effluents (Indigosol Green dye, Indigosol Purple dye, and Naphtol Black dye) and to investigate the ability of fungi on reducing TDS level. The study was also investigated the initial toxicity of batik effluents to Goldfish (Cyprinus carpio). Decolorization was measured by spectrophotometry, the pH value was measured by pH meter, and the TDS value was measured by TDS meter. In addition, the decolorized batik effluent was tested for toxic effect on C. carpio by total opercular beats. Decolorization assay showed that Aspergillus sp. 3 had the ability to decolorized only 2 kinds of batik effluents. The decolorization percentage of Indigosol Purple was 60.015% and Naphtol Black was 56.679%. The pH after treatment decreased from 8.5–9 to 5.3–6. The range of pH value of Indigosol Green, Indigosol Purple, and Naphtol Black 5.3–6. Besides that, Aspergillus sp. 3 also had the ability to reduce the TDS level in the effluent. The TDS level on Indigosol Green, Indigosol Purple, and Naphtol Black as 4,965%, 25,307%, and 15,129%, respectively. Initial toxicity assay of effluent to C. carpio showed that there was a difference of total opercular beats, which exposed by decolorized and before decolorized batik effluent. The total opercular beats of C. carpio on decolorized batik effluents showed high value than before decolorized batik effluents. It can be concluded that Aspergillus sp. 3 had the ability to decolorize and decreasing the initial toxicity of Indigosol Purple batik effluents on C. carpio.